Characterization of a membrane‐separated and a membrane‐less electrobioreactor for bioelectrochemical syntheses. Issue 7 (16th April 2018) - Krieg, Thomas; Phan, Linh M. P.; Wood, Jeffery A.; Sydow, Anne; Vassilev, Igor; Krömer, Jens O.; Mangold, Klaus‐Michael; Holtmann, Dirk
Abstract: Bioelectrochemical systems (BESs) have the potential to contribute to the energy revolution driven by the new bio‐economy. Until recently, simple reactor designs with minimal process analytics have been used. In recent years, assemblies to host electrodes in bioreactors have been developed resulting in so‐called "electrobioreactors." Bioreactors are scalable, well‐mixed, controlled, and therefore widely used in biotechnology and adding an electrode extends the possibilities to investigate bioelectrochemical production processes in a standard system. In this work, two assemblies enabling a separated and non‐separated electrochemical operation, respectively, are designed and extensively characterized. Electrochemical losses over the electrolyte and the membrane were comparable to H‐cells, the bioelectrochemical standard reaction system. An effect of the electrochemical measurements on pH measurements was observed if the potential is outside the range of −1, 000 to +600 mV versus Ag/AgCl. Electrobiotechnological characterization of the two assemblies was done using Shewanella oneidensis as an electroactive model organism. Current production over time was improved by a separation of anodic and cathodic chamber by a Nafion® membrane. The developed electrobioreactor was used for a scale‐up of the anaerobic bioelectrochemical production of organic acids and lysine from glucose using an engineered Corynebacterium glutamicum . Comparison to a small‐scale custom‐made electrobioreactor indicates that anodic electro‐fermentation of lysine and organic acids might not be limited by the BES setup but by the biocatalysis of the cells. Abstract : In this work, two assemblies enabling a separated and non‐separated electrochemical operation were designed and characterized. Current production over time was improved by a separation of anodic and cathodic chamber by a membrane. The developed electrobioreactor was used for a scale‐up of the bioelectrochemical production of organic acids from glucose using an engineered Corynebacterium glutamicum . Comparison to a small‐scale custom‐made electrobioreactor indicates that this electro‐fermentation might not be limited by the BES setup but by the biocatalysis of the cells.